PSYCHOLOGY OF THE UNDERSTANDING PROCESS AS A PREVAILING PROCESS OF CREATIVE MATHEMATICAL THINKING - Мойсеєнко, Л. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article considers issues concerning psychological essence of the understanding process in creative mathematical thinking. Modern scientific approaches to the investigation of creative thinking have been described. There has been pointed out the identification signs of human thinking activity in the field of mathematics. The issues connected with the psychological essence of understanding process have been examined. Moreover, the analysis was conducted of procedural-dynamic aspect of the understanding process as a component of creative mathematical thinking process directed to the solution of mathematical problems. The article proves the prevailing character of this process and its interconnection with other components (process of solution forecasting and approbation process of thinking results).